Coping Strategies Among Mothers of Children with Special Needs: A Phenomenological Study Using the SOAR Framework - Lintang Songgo Langit; Anniez Rachmawati Musslifah; Dhian Riskiana Putri (STAI Auliaurrasyidin Tembilahan, 2026)
Mothers of children with special needs are vulnerable to parenting stress arising from psychological, social, and economic challenges associated with caregiving. This study explored mothers’ experiences of parenting stress, identified the coping strategies they employed, and developed coping enhancement recommendations using the SOAR (Strengths, Opportunities, Aspirations, Results) framework. A qualitative phenomenological design was employed, involving three mothers from the Pejuang Buah Hati Wonogiri (Jatigiri) community. Data were collected through in-depth semi-structured interviews and analyzed using Colaizzi’s phenomenological method, followed by SOAR analysis to formulate strengths-based recommendations. The findings indicate that coping strategies evolved dynamically from less adaptive responses during the initial stage of diagnosis toward more adaptive emotion-focused and problem-focused coping as mothers developed greater self-acceptance, knowledge, and social support. The SOAR analysis further identified internal strengths and external opportunities that could strengthen mothers’ coping capacities. Based on these findings, coping-enhancement recommendations were formulated to improve parenting competencies, children’s independence, social support, family economic resilience, and mothers’ psychological well-being. These findings provide practical guidance for counselors, family support workers, community organizations, and local governments in developing comprehensive support programs for mothers of children with special needs.